2011
DOI: 10.3727/0963689109x546562
|View full text |Cite
|
Sign up to set email alerts
|

Cell Contact Accelerates Replicative Senescence of Human Mesenchymal Stem Cells Independent of Telomere Shortening and p53 Activation: Roles of Ras and Oxidative Stress

Abstract: Mesenchymal stem cells (MSCs) are of great therapeutic potentials due to their multilineage differentiation capabilities. Before transplantation, in vitro culture expansion of MSCs is necessary to get desired cell number. We observed that cell contact accelerated replicative senescence during such process. To confirm the finding as well as to investigate the underlying mechanisms, we cultured both human bone marrow-and umbilical cord blood-derived MSCs under noncontact culture (subculture performed at 60-70% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“…Ho et al . reported that the cell‐to‐cell contact‐induced senescence model is a useful system for investigating the molecular mechanisms of MSC senescence (24). They reported that cell‐to‐cell contact accelerated the senescence of human MSCs independently of telomere shortening and p53 activation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho et al . reported that the cell‐to‐cell contact‐induced senescence model is a useful system for investigating the molecular mechanisms of MSC senescence (24). They reported that cell‐to‐cell contact accelerated the senescence of human MSCs independently of telomere shortening and p53 activation.…”
Section: Resultsmentioning
confidence: 99%
“…Although direct contact between cells plays an important role in maintaining the organization of specialized tissues in various organisms, it can induce growth arrest in various cells and change their cell fate through transcriptional regulation (22, 23). In BM‐MSCs, cell‐cell contact can promote replicative cellular senescence via marked increases in intracellular reactive oxygen species and p16 (24). Thus, growth inhibition and alteration of cell fate by physical interaction are well known and predictable in BM‐MSC cultures.…”
mentioning
confidence: 99%
“…Contact culture at 100% confluence significantly increases ROS levels and promotes MSC senescence without influencing expression levels of telomerase reverse transcriptase (TERT) and p53 . Moreover, when added to the culture medium, multiple factors have a negative impact on MSC properties.…”
Section: Surrounding Microenvironments For Regulating Ros Production mentioning
confidence: 99%
“…On the long run in vitro cultivated MSCs display replicative senescence as independently demonstrated by a number of investigators Estrada et al 2013 ;Ho et al 2011 ;Hao et al 2013 ;Gruber et al 2012 ;Tsai et al 2010 ;Ksiazek 2009 ;Napolitano et al 2007 ). On the long run in vitro cultivated MSCs display replicative senescence as independently demonstrated by a number of investigators Estrada et al 2013 ;Ho et al 2011 ;Hao et al 2013 ;Gruber et al 2012 ;Tsai et al 2010 ;Ksiazek 2009 ;Napolitano et al 2007 ).…”
Section: Msc Aging In Vitromentioning
confidence: 81%